Conservation of the primosome in successive stages of phi X174 DNA replication. - Low, R L (1981)
Synthesis of a complementary strand to match the single-stranded, circular, viral (+) DNA strand of phage phi X174 creates a parental duplex circle (replicative form, RF). This synthesis is initiated by the assembly and action of a priming system, called the primosome [Arai, K. & Kornberg, A (1981) Proc. Natl. Acad. Sci. USA 78, 69-73; Arai, K., Low, R. L. & Kornberg, A. (1981) Proc. Natl. Acad. Sci. USA 78, 707-711]. Of the seven proteins that participate in the assembly and function of the primosome, most all of the components remain even after the DNA duplex is completed and covalently sealed. Remarkably, the primosome in the isolated RF obviates the need for supercoiling of RF by DNA gyrase, an action previously considered essential for the site-specific cleavage by gene A protein that starts viral strand synthesis in the second stage of phi X174 DNA replication. Finally, priming of the synthesis of complementary strands on the nascent viral strands to produce many copies of progeny RF utilizes the same primosome, requiring the addition only of prepriming protein i. thus a single primosome, which becomes associated with the incoming viral DNA in the initial stage of replication, may function repeatedly in the initiation of complementary strands at the subsequent stage of RF multiplication. These patterns of phi X174 DNA replication suggest that a conserved primosome also functions in the progress of the replicating fork of the Escherichia coli chromosome, particularly in initiating the synthesis of nascent (Okazaki) fragments.